Understanding Policy Failure in Pakistan: Structural Mechanisms and Cross-National Learning - Rizwan Ashraf; Amna Mahmood, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
Political failure in Pakistan has remained a persistent and multidimensional phenomenon, manifesting in governance breakdowns, institutional fragility, policy inconsistency, and recurrent democratic reversals. This paper seeks to develop a structured understanding of political failure in Pakistan by examining its underlying structural mechanisms and drawing comparative insights from cross-national experiences. The paper conceptualizes political failure as a systemic outcome produced through the interaction of institutional design, civil-military imbalance, weak accountability frameworks, elite capture, and constrained state capacity. The paper also discovers reform paths pursued by comparatively successful countries that overcame similar circumstances of instability and moved towards institutionalization. By combining structural explanations with cross-national learning, the paper helps to inform theoretical discourses on state failure and democratic weakness while providing policy-relevant knowledge for institutional transformation in Pakistan. This research uses a qualitative, comparative methodology with case study of Pakistan, rooted in the traditions of political economy and institutionalism. The results seek to shift the discussion from normative arguments to more analytically informed explanations that can help to support sustainable political and governance transformations.